2015
DOI: 10.1039/c5nj01126d
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the polar core size and external organic media composition on micelle–micelle interactions: the effect on gold nanoparticle synthesis

Abstract: An easy way to modulate reverse micelles as nanoreactors to produce different kinds of gold nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Organic solvent is both the extractant of target analytes in 2p‐HF‐LPME or 3p‐HF‐LPME‐RM and the media forming reverse micelle in 3p‐HF‐LPME‐RM. Aliquat 336 in different organic solvents can form various structures and sizes of reverse micelles . In this study, Aliquat 336 reverse micelles respectively prepared by dissolving certain amount in n ‐hexanol, n‐ heptanol, n ‐octanol, n ‐nonanol, and n ‐decanol were applied to extract the target analytes, and the results were compared with those of 2p‐HF‐LPME.…”
Section: Resultsmentioning
confidence: 99%
“…Organic solvent is both the extractant of target analytes in 2p‐HF‐LPME or 3p‐HF‐LPME‐RM and the media forming reverse micelle in 3p‐HF‐LPME‐RM. Aliquat 336 in different organic solvents can form various structures and sizes of reverse micelles . In this study, Aliquat 336 reverse micelles respectively prepared by dissolving certain amount in n ‐hexanol, n‐ heptanol, n ‐octanol, n ‐nonanol, and n ‐decanol were applied to extract the target analytes, and the results were compared with those of 2p‐HF‐LPME.…”
Section: Resultsmentioning
confidence: 99%
“…60 Furthermore, the micelle−micelle interactions and the water structure inside reverse micelles can be altered by the type or composition of the nonpolar phase. 13,60 Thus, it was found that when aromatic solvents are used, intermicellar interactions are weaker than in aliphatic solvents. As a consequence of this fact, a notable impact on the practical applications of reverse micelles as nanoreactors can be produced.…”
Section: Grmentioning
confidence: 99%
“…As a consequence of this fact, a notable impact on the practical applications of reverse micelles as nanoreactors can be produced. 13,60 For example, in the synthesis of nanoparticles, one of the key steps that controls the synthetic pathway is the coalescence process. In this sense, the intermicelle interactions can be controlled by the nature of the nonpolar solvent.…”
Section: Grmentioning
confidence: 99%
“…The synthesis of monometallic 50 and bimetallic NPs in RMs is described in the Supporting Information. This methodology is based in Brownian motion of RMs and in micelle−micelle interactions.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%